"Getting pregnant during COVID-19 was a big risk because getting help from the clinic was not easy": COVID-19 experiences of women and healthcare providers in Harare, Zimbabwe. - Zivai Mupambireyi; Frances M Cowan; Elizabeth Chappell; Anesu Chimwaza; Ngoni Manika; Catherine J Wedderburn; Hannah Gannon; Tom Gibb; Michelle Heys; Felicity Fitzgerald; Simbarashe Chimhuya; Diana Gibb; et al. (PLOS Global Public Health)
The COVID-19 pandemic and associated measures may have disrupted delivery of maternal and neonatal health services and reversed the progress made towards dual elimination of mother-to-child transmission of HIV and syphilis in Zimbabwe. This qualitative study explores the impact of the pandemic on the provision and uptake of prevention of mother-to-child transmission (PMTCT) services from the perspectives of women and maternal healthcare providers. Longitudinal in-depth interviews were conducted with 20 pregnant and breastfeeding women aged 20-39 years living with HIV and 20 healthcare workers in two maternity polyclinics in low-income suburbs of Harare, Zimbabwe. Semi-structured interviews were held after the second and third waves of COVID-19 in March and November 2021, respectively. Data were analysed using a modified grounded theory approach. While eight antenatal care contacts are recommended by Zimbabwe's Ministry of Health and Child Care, women reported only being able to access two contacts. Although HIV testing, antiretroviral therapy (ART) refills and syphilis screening services were accessible at first contact, other services such as HIV-viral load monitoring and enhanced adherence counselling were not available for those on ART. Closure of clinics and shortened operating hours during the second COVID-19 wave resulted in more antenatal bookings occurring later during pregnancy and more home deliveries. Six of the 20 (33%) interviewed women reported giving birth at home, assisted by untrained traditional midwives as clinics were closed. Babies delivered at home missed ART prophylaxis and HIV testing at birth despite being HIV-exposed. Although women faced multiple challenges, they continued to attempt to access services after delivery. These findings underline the importance of investing in robust health systems that can respond to emergency situations to ensure continuity of essential HIV prevention, treatment, and care services.